Lock cylinder, first key and second key - LIU XIAOJUN; FANG SICONG; ZENG GUOHUI (2024)
The utility model discloses a lock cylinder, a first key and a second key. The lock cylinder comprises a lock shell and a lock liner. A lock case; the lock cylinder is detachably mounted in the lock shell and comprises an anti-disassembly device, one end of the lock cylinder extends out of the lock shell, one end of the lock cylinder comprises a first mounting groove, the anti-disassembly device is inserted into the first mounting groove, and the anti-disassembly device can retract into the first mounting groove so that the lock cylinder can be disassembled relative to the lock shell; the anti-disassembly device can stretch out of the first installation groove and abut against the side wall of the lock shell so as to limit disassembly of the lock cylinder relative to the lock shell. The lock cylinder provided by the embodiment of the utility model comprises the lock shell and the lock liner, and the lock shell and the lock liner can be detached, so that the lock cylinder is convenient to maintain. 本实用新型公开一种锁芯